KONTRIBUSI TOPIK-TOPIK PRAGMATIK UNTUK BAHASA INDONESIA DI PERGURUAN TINGGI - Nesi, Antonius (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Abstract: Pragmatic Topics Contribution for Indonesian Language in College.  This article is concerned with the description of pragmatic topics. Each  topic has contribution toward the learning of Indonesian language in higher education. Studies  on  the previous relevant publications  emphasized mainly on  context. The discussion deals with  the nature of pragmatics based on the references. Accordingly, pragmatics  covers more specifically such topics as speech act, cooperative principle, pre-supposition and politeness. The analysis of each topic was followed by those contributions in learning Indonesia language. The results of analysis show that the pragmatic topics are relevant to learning when integrated in listening, speaking, reading and writing skill. Therefore, the ultimate goal of learning Indonesian language is achieved through  the students’ communicative competence.                                                                                                                                   Key words: pragmatics, Indonesian language, higher education, skill, communicative competence            Abstrak: Kontribusi Topik-topik Pragmatik untuk Bahasa Indonesia di Perguruan Tinggi. Artikel ini mendeskripsikan topik-topik pragmatik. Setiap topik memiliki kontribusinya untuk pembelajaran bahasa Indonesia di perguruan tinggi. Telaah terhadap publikasi-publikasi terdahulu yang relevan diletakkan sebagai konteks masalah. Pembahasan meliputi hakikat pragmatik yang didasarkan pada referensi-referensi. Selanjutnya, topik-topik pragmatik yang meliputi tindak tutur, prinsip kerja sama, praanggapan, dan kesantunan berbahasa diuraikan. Uraian setiap topik disusul langsung dengan kontribusinya dalam pembelajaran bahasa Indonesia. Hasil analisis menggambarkan bahwa topik-topik pragmatik relevan untuk pembelajaran bila diintegrasikan dalam keterampilan menyimak, berbicara, membaca, dan menulis. Dengan itu, tujuan akhir pembelajaran bahasa Indonesia tercapai, yaitu mahasiswa memiliki kompetensi komunikatif.                                                      Kata kunci: pragmatik, Bahasa Indonesia, perguruan tinggi, keterampilan, kompetensi komunikatif